Feminist judgments as teaching resources - Hunter, Rosemary C. (Oñati Socio-Legal Series, 2012)
This paper discusses feminist judgments as a specific vehicle for teaching students to think critically about law. The analysis of appellate judgments forms a central plank of Anglo-Commonwealth and US jurisprudence and legal education. While academic scholarship generally offers various forms of commentary on decided cases, feminist judgment-writing projects have recently embarked on a new form of critical scholarship. Rather than critiquing judgments from a feminist perspective in academic essays, the participants in these projects have set out instead to write alternative judgments, as if they had been one of the judges sitting on the court at the time. After introducing the UK Feminist Judgments Project and describing what is ‘different’ about the judgments it has produced, the paper explains some of the ways in which these judgments have been used in UK law schools to teach critical thinking. The paper finally speculates on the potential production and application of feminist judgments or their equivalents beyond the common law context.